Evaluation of cross-protection between S. Pneumoniae serotypes 35B and 29 in a mouse model. Issue 11 (10th March 2023) - Kim, Ellie; He, Jian; Kaufhold, Robin M.; McGuinness, Debra; McHugh, Patrick; Nawrocki, Denise; Xie, Jinfu; Skinner, Julie M.
Abstract: Pneumococcal conjugate vaccines (PCVs) have reduced vaccine-type pneumococcal disease but in turn have also resulted in replacement with non-vaccine serotypes. One such serotype, 35B, a multidrug resistant type, has been associated with an increase in disease. Mice were immunized intramuscularly with monovalent pneumococcal polysaccharide 35B conjugated to CRM197 containing aluminum phosphate adjuvant on days 0, 14, and 28. Pneumococcal enzyme-linked immunosorbent assay, opsonophagocytic killing assays, and competition OPA were performed for STs 35B and 29 to measure serotype-specific binding and functional antibodies. On day 52, mice were intratracheally challenged with S. pneumoniae ST29 to evaluate cross-protection. 35B-CRM197 immunized mice had binding and functional antibodies to both PnPs 35B and 29. 35B-CRM197 immunized mice were 100% protected from IT challenge with S. pneumoniae ST29 as compared to 30% survival in the naïve group. Future vaccines containing polysaccharide 35B, such as the investigational 21-valent PCV, V116, may provide cross protection against the non-vaccine serotype 29 due to structural similarity.